143 TEHNOLOGIA DE FORMARE A COMPETENŢEI DIGITALE PRIN INCLUDEREA MANUALULUI ELECTRONIC ÎN PROCESUL DIDACTIC REAL - USM ADMIN (Moldova State University, 2007)
The rapidly increasing use of computer in the didactic process, and in particular, the migration of many university courses to web-based education, has caused a resurgence of interest among specialists in the science of education in non-traditional methods of course design and delivery. This article provides some results of the applied three-dimensional model in design of electronic textbooks for the study of informatics. First, some of the theoretical approaches are listed. Then, some of the common problems are described, and solutions are pointed to in the literature and practical applica- tions. Finally, the main result is analyzed: the possibility to obtain curve J by means of including an electronic textbook in the real didactic process.